Legal Impact of the Division of Joint Rights to Land on the Obligation To Pay Land and Building Rights Acquisition Fees (Bphtb) - Widya Anugrah, Valentin; Purnawan, Amin (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
The Deed of Joint Ownership Distribution (APHB) in relation to the obligation to pay the Duty on the Acquisition of Land and Building Rights (BPHTB) is a crucial issue in Indonesia's land and taxation law practice. Juridically, the APHB is declarative in nature because it merely confirms the division of jointly owned property without creating new ownership rights. However, in practice, regional governments interpret the APHB differently when determining whether it is subject to BPHTB or not. This inconsistency has created legal uncertainty and inequality among citizens, as the tax burden imposed is often disproportionate to the legal benefits received. Therefore, a clear and harmonized legal framework is necessary to ensure that the application of BPHTB to APHB is consistent with the principles of legal certainty and justice. This research employs a normative legal research method using the statutory approach, conceptual approach, and case approach. The legal materials used consist of primary legal materials such as statutory regulations and court decisions, secondary legal materials such as literature and academic journals, and tertiary legal materials such as legal dictionaries. The data were analyzed descriptively and analytically by applying two main theories as analytical tools, namely Gustav Radbruch's Theory of Legal Certainty and Aristotle's Theory of Justice. The study reveals that an APHB without compensation does not create a new legal right and therefore should not be subject to BPHTB, whereas an APHB involving compensation constitutes a new legal acquisition and is thus taxable, as affirmed by the contitutional court No. 117/PUU-XXI/2023. However, the absence of explicit regulation in Law No. 28 of 2009 on Regional Taxes and Levies has led to disharmony and inconsistent implementation among regions. Based on Radbruch's theory, this situation indicates a lack of legal certainty; while from Aristotle's perspective, the imposition of BPHTB without any economic gain violates the principle of distributive justice. Therefore, harmonization between the Ministry of Finance and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) is urgently needed to ensure fair, proportional, and consistent legal enforcement that provides both justice and certainty for society.